Combined treatment with anti-PSMA antibody and human peripheral blood-derived NK cells for castration-resistant prostate cancer - Wang, Fangming; Xing, Nianzeng; Li, Jianxing (Frontiers in Immunology, 2025)
BackgroundCastration-resistant prostate cancer (CRPC) has a poor prognosis and requires novel therapeutic approaches. Previously, we discovered that a high dose of human peripheral blood-derived natural killer (PB-NK) cells can have antitumor effects against CRPC. However, whether antibodies against prostate-specific membrane antigen (PSMA) can direct adoptive NK cells to the tumor site and therefore decrease NK cell dosage through antibody-dependent cellular cytotoxicity remains unknown.MethodsNK cells were obtained from the blood samples of healthy donors. To engineer an anti-PSMA antibody (Ab), a llama was immunized with human PSMA protein, and the anti-PSMA variable domains of camelid heavy-chain antibody (VHH) clones were isolated using phage display. The VHH was recombinantly fused with the human Fc region to produce an anti-PSMA Ab. In vitro, NK cell cytotoxicity was evaluated using cell counting kit-8. Levels of cytokines and prostate-specific antigen (PSA) were determined using ELISA. The expression of CD107a and CD16 (the Ab Fc-receptor) in NK cells and the Ab affinity were detected using flow cytometry. Antitumor effects were evaluated in patient-derived organoid (PDO) models and in 22RV1 tumor-bearing mice in vivo.ResultsWe constructed an anti-PSMA Ab and validated its high affinity toward the PSMA antigen. CD16 is abundantly expressed in PB-NK cells. The anti-PSMA Ab significantly enhanced the cytotoxicity of NK cells against CRPC cells in vitro, evidenced by increased killing rate, upregulation of the degranulation marker CD107a, increased secretion of interferon-γ, and decreased PSA levels. Furthermore, our combined treatment showed powerful antitumor effects in PDO and CRPC xenograft mouse models.ConclusionCombined treatment with anti-PSMA Ab and human PB-NK cells improves antitumor efficacy against CRPC and is a promising approach to treating CRPC in clinical settings.